Study on Assignment Problem and its Extensions in Fuzzy Environment - Kant, Bharti (My University, 2012)
In chapter 1st-literature review is presented. In chapter 2nd-Mukherjee and Basu[28] proposed a method for solving fuzzy assignment problems.Kumar and Gupta[20] have chosen some fuzzy assignment problems and fuzzy travelling salesman problems,which cannot by using the fore-mentioned method and propesed a new method for solving such type of fuzzy assignment problems and fuzzy travelling salesman problems. In this chapter,the existing method[20] is presented. In 3rd chapter-bai.et.al.[4] proposed a method for solving fuzzy generalized assignment problem. Kumar and Gupta[21] pointed out the limitation of existing method and proposed method.to overcome the limitation,in this chapter,the existing method[21] for solving the generalized fuzzy assignment problem is presented.
Master of Science (Mathematics and Computing)
Keywords: Fuzzy assignment